Adapting to Sea‐Level Rise: Centralization or Decentralization in Polycentric Governance Systems?. Issue 1 (8th May 2021) - Lubell, Mark; Robbins, Matthew
Abstract : How do polycentric governance systems respond to the emergence of new collective‐action problems? We study this question in the context of the evolution of polycentric systems of sea‐level rise adaptation in the San Francisco Bay Area. We focus on how the structure of polycentric systems changes over time to support cooperation and learning and whether those changes represent a process of centralization or decentralization. The ecology of games framework provides the theoretical background for developing hypotheses about the structure of the system over time. We test the hypotheses by analyzing the polycentric system as a two‐mode network where actors are linked to policy, divided into five time periods from 1991 to 2016. The results suggest that the polycentric system for sea‐level rise adaptation started with a centralized set of actors, which evolved over time to a more decentralized structure. The research has general implications with respect to how polycentric systems manage the trade‐off between maintaining local autonomy and coordinating decisions at the regional level across fragmented policy communities. 摘要: 多中心治理系统如何对新的集体行动问题的出现进行响应？我们以旧金山湾海平面上升适应过程的多中心系统的发展为背景，对该问题进行了研究。我们聚焦于多中心系统结构如何随时间推移而发生变化（用于支持合作和学习），并聚焦于这些变化是否代表了中心化过程或去中心化过程。博弈生态学框架为关于该系统随时间推移的结构变化假设提供了理论背景。我们检验了这些假设，检验方式则是将多中心系统作为一个具备两种模式的网络加以分析，在该网络中，行动者与政策相联系，并被划分到1991‐2016年的5个时间段内。分析结果暗示，海平面上升适应过程的多中心系统最初以中心化的行动者开始，并随时间推移而发展为更为去中心化的结构。就多中心系统如何管理"维持地方自治"和"在分散的政策社区之间协调地区决策"这二者间的得失而言，本研究具有普遍意义。 Resumen: ¿Cómo responden los sistemas de gobernanza policéntrica al surgimiento de nuevos problemas de acción colectiva? Estudiamos esta cuestión en el contexto de la evolución de los sistemas policéntricos de adaptación al aumento del nivel del mar en el Área de la Bahía de San Francisco. Nos enfocamos en cómo la estructura de los sistemas policéntricos cambia con el tiempo para apoyar la cooperación y el aprendizaje, y si esos cambios representan un proceso de centralización o descentralización. El marco de la ecología de los juegos proporciona los antecedentes teóricos para desarrollar hipótesis sobre la estructura del sistema a lo largo del tiempo. Probamos las hipótesis analizando el sistema policéntrico como una red de dos modos donde los actores están vinculados a la política, divididos en cinco períodos de tiempo desde 1991 a 2016. Los resultados sugieren que el sistema policéntrico para la adaptación al aumento del nivel del mar comenzó con un conjunto centralizado de actores, que evolucionó con el tiempo hacia una estructura más descentralizada. La investigación tiene implicaciones generales con respecto a cómo los sistemas policéntricos gestionan el equilibrio entre mantener la autonomía local y coordinar las decisiones a nivel regional en comunidades de políticas fragmentadas.